Thermo-Hydraulic Analysis of a Tri-Axial High-Temperature Superconducting Power Cable with Respect to Installation Site Geography - Youngjun Choi; Dongmin Kim; Changhyung Lee; Duyeon Won; Jaeun Yoo; Hyungsuk Yang; Seokho Kim (Energies, 2020)
Various high-temperature superconducting (HTS) power cables are being developed or are ready for commercial operation to help energy suppliers meet the growing power demand in urban areas. Recently, triaxial HTS power cables have been developed by Korea Electric Power Corporation (KEPCO) and LS Cable & System. Further, KEPCO has been planning to install a 2 km long 23 kV/60 MVA triaxial HTS power cable to connect the Munsan and Seonyu substations and increase the stability of the power grid. The HTS power cables should be cooled down to a cryogenic temperature near 77 K. A thermo-hydraulic analysis of the cooling system considering the geographical characteristics of the installation site is essential for long-distance sections. This paper describes the thermo-hydraulic analysis of the triaxial HTS power cable to determine the proper mass flow rates of subcooled liquid nitrogen that meet the operating temperature and pressure of the cable for four configurations of cooling systems: (1) a single cooling system with an external return path, (2) a dual cooling system with an external return path, (3) a single cooling system with an internal return path, and (4) a dual cooling system with internal return path. Since the flow characteristics in a corrugated cable cryostat differ significantly from those in a typical annular tube, a computational fluid dynamics (CFD) analysis was conducted to estimate the pressure drop along the cable cryostat. With the CFD analysis and given heat loads in the cable, the temperature and the pressure variations along the cable were calculated and their pros and cons were compared for each configuration of the cooling system. This thermo-hydraulic analysis will be referenced in the actual installation of the HTS power cable between the Munsan and Seonyu substations.